2013
DOI: 10.1371/journal.pone.0078994
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ‘Variable Number of Tandem Repeat’-Based Approach for Examination of ‘Candidatus Liberibacter asiaticus’ Diversity and Its Applications for the Analysis of the Pathogen Populations in the Areas of Recent Introduction

Abstract: Citrus greening (Huanglongbing, HLB) is one of the most destructive diseases of citrus worldwide. In South Asia HLB has been known for more than a century, while in Americas the disease was found relatively recently. HLB is associated with three species of ‘Candidatus Liberibacter’ among which ‘Ca. Liberibacter asiaticus’ (CLas) has most wide distribution. Recently, a number of studies identified different regions in the CLas genome with variable number of tandem repeats (VNTRs) that could be used for examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
0
14
0
7
Order By: Relevance
“…Psyllid DNA was extracted from three sub-samples of each population, using the DNeasy Blood & Tissue Kit (Qiagen, Venlo Netherlands) as reported for the extraction of DNA from the Asian citrus psyllid, Diaphorina citri [ 31 ]. DNA from twenty psyllids (a group) was extracted using the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Psyllid DNA was extracted from three sub-samples of each population, using the DNeasy Blood & Tissue Kit (Qiagen, Venlo Netherlands) as reported for the extraction of DNA from the Asian citrus psyllid, Diaphorina citri [ 31 ]. DNA from twenty psyllids (a group) was extracted using the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…They hypothesized that the pathogen was likely introduced to Thailand from China and/or the Philippines based on their phylogenetic analyses. Matos et al (2013) used four microsatellite markers to investigate diversity from HLB isolates from Florida, USA, Mexico and various parts of the Caribbean. Similarly to Chen et al (2010), lower genotypic diversity was found in Florida compared to the other regions sampled where the disease has been prevalent for a longer period of time.…”
Section: Population Biology Of 'Ca Liberibacter' Speciesmentioning
confidence: 99%
“…MLVA was used in an epidemiological survey to trace the routes of Haemophilus influenzae outbreaks (8) or Bacillus anthracis (2,9) outbreaks. MLVA was applied to monomorphic plant-pathogenic bacteria belonging to different genera and species such as Xylella fastidiosa (10), Xanthomonas citri (11), Ralstonia solanacearum (12), "Candidatus Liberibacter asiaticus" (13), Erwinia amylovora (14), and Xanthomonas arboricola pathovars (15). MLVA was first applied on Pseudomonas syringae by Gironde and Manceau (16) and provided new insights into host specificity of P. syringae pathogenic on brassicaceous and solanaceous plants.…”
mentioning
confidence: 99%